Adat Istiadat dan Faktor-Faktor Yang Dapat Menghilangkannya (Studi Kasus di Kecamatan Sawang Kabupaten Aceh Selatan) - Subhi, Muhibbul; Nova, Mirza Adia; Nasir, M.; Samwil, Samwil; Ridha, Ismu; Syam, Futri; Nafisah, Raudhatun (AL-UKHWAH - JURNAL PENGEMBANGAN MASYARAKAT ISLAM, 2024)
Abstract This article attempts to discuss about the factors that can eliminate customs in an area. Customs are behaviors that a community of people for generations. Customs may also transform from time to time according to developments over time, customs can even disappear from an area due to several supporting factors. This research started with the question, how can the customs disappear from an area. This research uses a descriptive analysis study, namely analyzing the social phenomena of the Sawang community in carrying out traditional processions. Data was obtained from informants who knew about customs; traditional leaders, religious leaders, scholars and several communities in Sawang District, South Aceh Regency. The research results show that customs will be lost due to several factors such as tsunamis, the arrival of foreign cultures, the disappearance of scholars, and the influence of technology and major wars. We have seen many of these four factors and have proven effective in eliminating customs in a place. Keywords: Factor, Eliminate, Costums, Culture, Aceh.